2010
DOI: 10.1007/s10336-009-0487-y
|View full text |Cite
|
Sign up to set email alerts
|

Arrival timing and hematological parameters in Gray Catbirds (Dumetella carolinensis)

Abstract: Early arrival at the breeding grounds for migratory birds is associated with greater reproductive success. According to the condition-dependent arrival hypothesis, only those individuals in superior physiological condition are able to bear the costs (e.g., poor environmental conditions, limited food availability) of early arrival. Condition has usually been measured in terms of energy reserves or mass but other physiological measures of condition such as hematocrit and immune function have been gaining attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
1
14
1
2
Order By: Relevance
“…In support of this, we found that males arriving with high androgen have high haematocrit. Further, in agreement with previous studies (Ninni et al 2004, Hatch et al 2010), we found that haematocrit was positively associated with early arrival. Together, these findings suggest that males who elevate androgen benefit from associated erythropoietic effects, increasing oxygen capacity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In support of this, we found that males arriving with high androgen have high haematocrit. Further, in agreement with previous studies (Ninni et al 2004, Hatch et al 2010), we found that haematocrit was positively associated with early arrival. Together, these findings suggest that males who elevate androgen benefit from associated erythropoietic effects, increasing oxygen capacity.…”
Section: Discussionsupporting
confidence: 93%
“…However, researchers have repeatedly found that changes in haematocrit are a physiological component of the migratory state, often independent of energetic condition. Haematocrit increases in migratory birds around the time of migration (Wingfield and Farner 1980, Bairlein and Totzke 1992, Morton 1994, Piersma et al 1996), decreases following arrival at breeding areas in males (Saino et al 1997), and has been positively associated with early arrival (Ninni et al 2004, Hatch et al 2010). Androgen‐induced erythrocyte synthesis could result in greater oxygen carrying capacity during migration in birds, increasing flight performance.…”
mentioning
confidence: 99%
“…ISSN 0004-8038, electronic ISSN 1938-4254. © (Hatch et al 2010, Knowles et al 2010. Although the widespread use of these techniques has opened many new and exciting lines of inquiry, with the increased regularity of blood collection comes an increased need for researchers to ensure that they safely handle birds and minimize threats to survival.…”
Section: Análisis Multiestado De Marcado-recaptura Revela Ausencia Dementioning
confidence: 99%
“…Within populations, phenotypic correlations have been established between arrival dates and wing shape (Bowlin, 2007; Choi et al. , 2010) and arrival dates and individual condition (Hatch et al. , 2010).…”
Section: Introductionmentioning
confidence: 99%